Design, Synthesis and Biological Assessment of Rhodanine-Linked Benzenesulfonamide Derivatives as Selective and Potent Human Carbonic Anhydrase Inhibitors - Baijayantimala Swain; Abrar Khan; Priti Singh; Vaibhav S. Marde; Andrea Angeli; Krishna Kartheek Chinchilli; Venkata Madhavi Yaddanapudi; Simone Carradori; Claudiu T. Supuran; Mohammed Arifuddin (Molecules, 2022)
A novel series of twenty-five rhodamine-linked benzenesulfonamide derivatives (7a–u and 9a–d) were synthesized and screened for their inhibitory action against four physiologically relevant human (h) carbonic anhydrase (CA) isoforms, namely hCA I, hCA II, hCA IX, and hCA XII. All the synthesized molecules showed good to excellent inhibition against all the tested isoforms in the nanomolar range due to the presence of the sulfonamide as a zinc binding group. The target compounds were developed from indol-3-ylchalcone-linked benzenesulfonamide where the indol-3-ylchalcone moiety was replaced with rhodanine-linked aldehydes or isatins to improve the inhibition. Interestingly, the molecules were slightly more selective towards hCA IX and XII compared to hCA I and II. The most potent and efficient ones against hCA I were 7h (KI 22.4 nM) and 9d (KI 35.8 nM) compared to the standard drug AAZ (KI 250.0 nM), whereas in case of hCA II inhibition, the derivatives containing the isatin nucleus as a tail were preferred. Collectively, all compounds were endowed with better inhibition against hCA IX compared to AAZ (KI 25.8 nM) as well as strong potency against hCA XII. Finally, these newly synthesized molecules could be taken as potential leads for the development of isoform selective hCA IX and XII inhibitors.